Endocrine disruptors and bladder function: the role of phthalates in overactive bladder - Liu, Li; Li, Xia; Hao, Xuexue; Xu, Zhunan; Wang, Qihua; Ren, Congzhe; Li, Muwei; Liu, Xiaoqiang (Frontiers in Public Health, 2024)
BackgroundPhthalates, widely used as plasticizers, are pervasive environmental contaminants and endocrine disruptors. Their potential role in overactive bladder (OAB) pathogenesis is underexplored, necessitating further investigation into their impact on OAB using large-scale epidemiological data.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2011 to 2018. A weighted multivariable logistic regression model was employed to examine the relationship between urinary phthalate concentrations and OAB. Subgroup analyses were conducted to explore differences in associations across various subgroups. Restricted cubic spline (RCS) analysis was used to investigate the potential non-linear relationship between urinary phthalate concentrations and OAB. Additionally, Bayesian Kernel Machine Regression (BKMR) analysis was performed to explore the overall effects and interactions of phthalate mixtures.ResultsIn the multivariable logistic regression model fully adjusted for confounding variables, higher concentrations of MBzP and MiBP were associated with an increased risk of OAB, particularly in the highest tertiles (MBzP: OR = 1.401, 95% CI: 1.108–1.771; MiBP: OR = 1.050, 95% CI: 1.045–1.056). Subgroup analysis found that subgroup characteristics did not have a significant moderating effect on the association between phthalates and OAB. RCS analysis revealed a linear relationship between both MBzP and MiBP and OAB. BKMR analysis confirmed a positive overall effect of phthalate mixtures on OAB risk, with MBzP identified as the major contributing factor.ConclusionIn our study cohort, a positive correlation between urinary phthalate concentrations and OAB was observed, necessitating further research to validate and refine this conclusion.